A Modified Polygon Shaped Microstrip Patch Antenna Array for Ultra-Wideband Applications - Abdulnabi, Hussein Ali; Shurij, Mushreq A.; Sohrab, Ammar A. (Peneliti Teknologi Teknik Indonesia, 2023)
A single element and two elements array polygon shape microstrip antenna is proposed and analyzed in this paper for ultra-wideband (UWB) applications. The technique used to improve antenna performance is etching rectangular slots on the patch of the antenna with different dimensions and positions. Two Polygon Shape antenna patches are introduced to enhance the antenna properties. Also, multi-slots are reached to improve the antenna gain, impedance matching sweep parameter optimization technique is used to all antenna parameters to enhance antenna properties. The dimensions of the single element antenna are 30 x 33 mm2 and consist of a slotted polygon patch printed on an FR-4 substrate. The proposed antenna has a resonant frequency of 6.2 GHz, while the dimensions of two elements antenna array are 60 x 33 mm2 and the resonance frequency is 9.8 GHz. A technique of inset feed transmission line was utilized to match the 50 Ω microstrip feed line and the radiating patch. These considerations make the structure is suitable for fifth-generation generation (5G) mobile wireless applications. The proposed antenna was simulated by use Computer Simulation Technology (CST-2020) software.